Results from the UmWeltWandel Project in Al-Khashbah, Sultanate of Oman - Beuzen-Waller, Tara; Schmidt, Conrad; Pietsch, Dana; Proctor, Lucas; Unkelbach, Julia; Schmitt, Katharina (2026)
Despite the significant scarcity of water resources, human groups in Oman developed long-term strategies enabling sustainable occupation of drylands. These adaptive capacities were shaped over millennia of settlement in challenging and fluctuating environments that, over the past 10,000 years, experienced major shifts from humid to arid conditions driven by monsoon variability. Such climatic fluctuations profoundly influenced the availability of water, plant, and animal resources. The long-standing interactions between environment and early Omani societies, situated at the intersection of natural processes, climatic trends, and resource management strategies, are traceable in both archaeological and environmental records. The UmWeltWandel joint project (2020–2024) investigates the local-scale environmental evolution of the Al-Khashbah area in Oman through a multidisciplinary approach integrating geochemistry, geomorphology, geophysics, soil science, archaeobotany, and palynology. The project aims to reconstruct the long-term evolution of landscapes and resources in Central Oman over the last 10,000 years. This paper presents an overview of the project’s results, focusing on how the Al-Khashbah sector in the Ash Sharqiyah North Governorate evolved from the humid conditions of the Holocene Humid Period to the present arid climate, and how Bronze Age societies began to transform the surrounding landscape to optimize local resources around Al- Khashbah. By intensively investigating a single area through a multidisciplinary framework, this study both extracts new and challenging datasets and highlights the potential of selected environmental proxies for reconstructing human–environment interactions in Oman and, more broadly, in drylands.
Presenters: _:n205

Returning Places: Exploring Neolithic mobility and place persistence in the Hajar piedmont - Maiorano, Maria Pia; Proctor, Lucas; Maini, Elena; Harris, Joseph; Paulsen, Paige; Moreau, Jakez; Creamer, Petra; Sneberger, Jiri; Beuzen-Waller, Tara (2026)
Shifting the focus from the well-studied coast to the inland piedmont opens a new chapter in understanding the Neolithic of South Arabia. The HERDS in Oman Project at the site of KHS-A, near al-Khashbah, offers a rare opportunity to view Neolithic lifeways from an inland perspective... [Texte intégral respecté]
Presenters: _:n67

Bisya as an Early Bronze Age oasis landscape: results of 4 years of exploration - Jean, Mathilde; Sauvage, Martin; Beuzen-Waller, Tara; Munoz, Olivia; Proctor, Lucas; Rointru, Kaina; Mespoulet, Théo; Pietsch, Dana; Oufi, Ayoub al-; Tamimi, Ahmed al- (2026)
Bisya (Ad Dakhiliyah, Oman) has long been known as a major Bronze and Iron Ages centre in the Oman peninsula... [cite: 4]
Presenters: _:n315

Human Occupation of Central Oman during the Early Holocene - Chlachula, Dominik; Maiorano, Maria Pia; Hilbert, Yamandu; Beuzen-Waller, Tara; Beshkani, Amir; Arnold, Lee; Meredith-Williams, Matthew; Rose, Jeffrey; Usyk, Vitalii; Danielisova, Alžběta; Garba, Roman (2026)
This paper presents new evidence of Late/Final Palaeolithic occupation in central Oman... [cite: 4]
Presenters: _:n300